2003
DOI: 10.3402/meo.v8i.4338
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of the Professional Behavior of Faculty Physicians

Abstract: This study was conducted to obtain a baseline understanding of the professional behavior of clinical faculty physicians from the medical students' perspective. Students completed a professionalism evaluation of supervising faculty at the end of each required third-year clerkship over a one year period. Results were analyzed by specific behaviors and across clerkships. Differences were noted in the frequency of the types of problems seen, and varied by clerkship discipline. The most common transgressions of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…As many of these attributes represent behaviour that can be modified the authors concluded that providing advice and Teaching professionalism e287 training could help more physicians to become excellent role models. Szauter et al (2003) found that students had observed the following transgressions by role models in their faculty:…”
Section: Role Modelingmentioning
confidence: 99%
“…As many of these attributes represent behaviour that can be modified the authors concluded that providing advice and Teaching professionalism e287 training could help more physicians to become excellent role models. Szauter et al (2003) found that students had observed the following transgressions by role models in their faculty:…”
Section: Role Modelingmentioning
confidence: 99%
“…Describing other clinical services or other doctors in a derogatory manner accounted for 33.3% of the reports, while withholding or giving false information to patients and families, and treating non-physician health care workers in a disrespectful manner were observed in 22% and 11.1% of the cases, respectively. Of interest, Szauter et al reported that the most common transgressions of faculty were derogatory comments directed at other services, at patients, or towards a patient's family [3].…”
Section: Discussionmentioning
confidence: 99%
“…The first part of the questionnaire asked whether students ever witnessed unethical behaviour; whether it occurred during the preclinical or clinical years of study; whether the unethical behaviour witnessed was performed by a student, resident, senior physician, nurse or other; whether the student reported the unethical behaviour to anyone; and finally, if they discussed the event with their classmates. The second part of the questionnaire was based on one designed and utilized by [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings are reported in studies conducted in other universities. [14][15][16][17] Autonomy BCMP students engaged with the complexity of the consent process and subsequent challenges in obtaining informed consent. [15,18] Students referred to the 'dynamics of the consent process that are unique to South Africa' as they "The extended set of responsibilities that include the respectful, sensitive focus on individual patient needs that transcends the physician's self-interest, the understanding and use of the cultural dimension in clinical care, the support of colleagues, and the sustained commitment to the broader societal goals of medicine as a profession".…”
Section: Non-maleficence Justice and Human Rights Violationmentioning
confidence: 99%